Healthcare disparity and its associations with cytomegalovirus disease in pediatric liver transplant recipients in South Africa. Issue 6 (29th July 2022) - Walabh, Priya; Moore, David P.; Paget, Graham; Meyer, Anja; Moshesh, Porai Nthabaleng M.; Walabh, Pravina; Palweni, Sechaba T.; Hajinicolaou, Christina
Abstract: Background: Cytomegalovirus (CMV) infection and disease are preventable complications following pediatric liver transplantation (PLT), despite the use of prophylaxis to minimize the risk of CMV disease. We evaluated the incidence and complications of CMV disease in PLT recipients in South Africa (SA), with particular reference to potential differences in outcome between state and private sector patients. Methods: Medical records of patients younger than 16 years of age who received liver transplants between January 1, 2012, and August 31, 2018 were analyzed. Results: Records of all 150 PLT patients were retrieved. The median age at transplant was 29.2 months (95% confidence interval 15.6–58.4) and follow‐up was 46.3 months (interquartile range 27.6–63.1). Sixty‐six (44%) patients were high risk, 79 (52.7%) were intermediate risk, and five (3.3%) were low risk for CMV infection. Forty‐three (28.9%) patients had CMV DNAemia following transplantation, and 30 (20.1%) developed CMV disease. Receipt of care in the private sector was consistently associated with a lower hazard of CMV disease (adjusted hazard ratio [aHR] ranging from 0.36 to 0.43) and a consistently lower hazard of death among recipients at high risk for CMV disease and/or those who developed CMV disease (aHR ranging from 0.28 to 0.33). Conclusion: Receipt of care in the private health sector was associated with a consistently lower hazard of CMV disease and death in individuals with CMV disease and/or at high risk for CMV disease. Policies aimed at creating a more equitable healthcare system in SA may mitigate the differential burden of illness associated with CMV in PLT recipients. Abstract : Graphical abstract: